Avaliação da função do enxerto após uso da solução de conservação IGL1 ou UW no transplante hepático - Thais Gomes Casali (2013)
BACKGROUND: Wisconsin University (UW) solution remains as a reference for comparison between new products for graft preservation. Georges Lopes Institute (IGL1) solution had demonstrated good results in European studies: hepatocyte integrity was better preserved when compared to the UW solution and cellular parenchymal damage was reduced. METHODS: This randomized prospective study evaluated 43 liver transplants and analyzed the following data: clinical and laboratory profile of donors, liver enzymes levels and post-transplant complications. Statistical significance was considered when p < 0.05. RESULTS: UW was used in 21 cases whereas 22 used IGL1 preservation solution. Both donors groups had a similar clinical, hemodynamic and laboratory profile, without significant statistical differences. AST, ALT, LDH and total bilirrubin levels had similar values when both groups were compared. Hepatic artery thrombosis was evidenced in only one case which received the UW solution. Allograft dysfunction, primary nonfunction and death indices were similar between groups. Biliary strictures were approximately four times more prevalent in the UW group (19%) as compared to IGL1 (4.5%), p > 0.05. Biliary stricture incidence, however, was significantly higher in the UW group when a subgroup transplants from donors of less than 60 years of age was considered (p = 0.048). CONCLUSION: IGL1 solution had similar results to UW solution with regard to postoperative clinical outcomes in Brazilian population. Biliary strictures higher incidence in the UW solution should be further studied in a larger sample and with a focused methodology.